Information shocks and profitability risks for power plant investments: Impacts of policy instruments - Benjamin Botor; Benjamin Böcker; Thomas Kallabis; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2018)
Climate change mitigation requires governmental intervention, but different choices are at hand. While economists in general advocate for first-best instruments, reality looks quite different, with especially many subsidy schemes for renewable energies being used. Supporters of these schemes often argue that investment risk reduction is essential to achieve ambitious environmental targets. In this paper we compare four different instruments (cap, tax, minimum quota and feed-in tariffs/renewable auctions) in terms of efficacy and efficiency and also quantify investment risks, assuming an uncertain investment environment, represented by different information shocks on demand, investment and fuel cost. We use a long-term electricity market equilibrium model (generalized peak load pricing model) of the future German electricity market implemented as a linear optimization problem. Starting from an equilibrium, single input parameters are varied to simulate the arrival of new information. Running the model again with partly fixed capacities then allows us to analyze the adjustment of the power plant portfolio towards the new equilibrium over time. As expected quantity-based instruments are effective in assuring achievement of quantitative goals, notably a certain emission level. Yet risks for investors are rather high in that furthermore that first-best instruments are the most efficient. Risks are lower with price solutions, especially feed-in tariffs or renewable auctions provide the possibility to limit risks extremely by diversification only inside the electricity market.
Keywords: Q40; Q48; 330; Information shocks; Electricity system; Investment; Policy instruments